Malaysia listed technology companies: examining the optimal capital structure, financial ratios trend and financial health from 2012 to 2016 - Adilah Irdahwani, Abdul Rahim (2018)
Capital structure of the firm plays an important role to help firm achieves better performance and sustainability in its business. As such, this study was conducted to investigate the optimal capital structure, to observe financial ratio trends and to examine the financial health in the context of technology companies listed on KLTEC Index in Malaysia. The financial data of 30 technology companies listed on KLTEC Index were extracted from Bloomberg database for 5 years, which is from 2012 to 2016. The financial data were analyzed using Descriptive Analysis, Financial Ratio Analysis and Altman’s Z-Score. Descriptive analysis was used to investigate the optimal capital structure, the financial ratio analysis was used to see the profitability, tangibility and liquidity trends and Altman’s Z-Score Model was used to examine the financial health of the listed technology companies. The descriptive analysis summarized that most of the technology companies have acquired 71.3 per cent debt financing to finance its assets. The profitability ratio showed a declining trend for three (3) consecutive years from 2014 to 2016, the tangibility ratio showed moderate-tohealthy trend which ranged between 0.40 and 0.38 in 2012 and 2016 respectively, and the liquidity ratio indicated a stable trend which ranged between 3.15x to 3.04x from 2012 to 2016. The Altman’s Z-Score presented that the Green Packet Bhd, Omesti Bhd and HeiTech Padu Bhd have recorded the lowest Z-Score which portrayed high risk of bankruptcy.